Serine Biosynthesis Pathway Supports MYC–miR-494–EZH2 Feed-Forward Circuit Necessary to Maintain Metabolic and Epigenetic Reprogramming of Burkitt Lymphoma Cells - Emilia Białopiotrowicz (Cancers, 2020)
Burkitt lymphoma (BL) is a rapidly growing tumor, characterized by high anabolic requirements. The MYC oncogene plays a central role in the pathogenesis of this malignancy, controlling genes involved in apoptosis, proliferation, and cellular metabolism. Serine biosynthesis pathway (SBP) couples glycolysis to folate and methionine cycles, supporting biosynthesis of certain amino acids, nucleotides, glutathione, and a methyl group donor, S-adenosylmethionine (SAM). We report that BLs overexpress SBP enzymes, phosphoglycerate dehydrogenase (PHGDH) and phosphoserine aminotransferase 1 (PSAT1). Both genes are controlled by the MYC-dependent ATF4 transcription factor. Genetic ablation of PHGDH/PSAT1 or chemical PHGDH inhibition with NCT-503 decreased BL cell lines proliferation and clonogenicity. NCT-503 reduced glutathione level, increased reactive oxygen species abundance, and induced apoptosis. Consistent with the role of SAM as a methyl donor, NCT-503 decreased DNA and histone methylation, and led to the re-expression of ID4, KLF4, CDKN2B and TXNIP tumor suppressors. High H3K27me3 level is known to repress the MYC negative regulator miR-494. NCT-503 decreased H3K27me3 abundance, increased the miR-494 level, and reduced the expression of MYC and MYC-dependent histone methyltransferase, EZH2. Surprisingly, chemical/genetic disruption of SBP did not delay BL and breast cancer xenografts growth, suggesting the existence of mechanisms compensating the PHGDH/PSAT1 absence in vivo.